Educação literária na educação infantil: o livro nas mãos de professoras e educadoras de Araçatuba (SP) - Silveira, Roberta Caetano da [UNESP] (2014)
Joined to Childhood and Education, a line of work of Faculdade de Ciências e Tecnologia/Universidade Estadual Paulista‟s Post-graduate Program in Education, this research aims to investigate how the practice of two teachers and two early years educators occurs regarding to reading and storytelling. All of them work with the same four-year-old and five-year-old children in a full-time kindergarten in Araçatuba, State of São Paulo. It is necessary to identify their concepts and practices on reading and storytelling in order to verify whether they understand the importance of Children‟s Literature in the development and education of beginning readers. The questions are: do they merely read/tell stories or allow different practices of reading and storytelling techniques? Do they provide an educational work committed to the passage from children as listeners to students as readers, seeking to arouse in children, at first, a love of reading (the lust to hear stories) and, later, have them reading by themselves? The research is based on studies concerning the themes: Childhood Education; Children's Literature; reading; storytelling; teacher‟s training and reading education”, which give it theoretical consistency. This is a research in Education, of qualitative approach in a case study perspective and of ethnographic type...